The spiritual sources of legal crativity - Falk, Richard A. (Fordham University, New York, 2010)
This Inaugural Miguel D´Escoto Lecture celebrates an important anniversary in internatinal law and the remarkable man who was the moving force behind a landmark case affirming the rights of small nations in world of proxy wars and illegal boycotts